Keeping Pace With Water and Wastewater Rates. Issue 10 (1st October 2017) - Stratton, Hannah; Fuchs, Heidi; Chen, Yuting; Dunham, Camilla; Ni, Chun Chun; Williams, Alison
Abstract : Water and wastewater treatment and delivery are the most capital‐intensive of all utility services. The literature indicates that historically underpriced water and wastewater rates have exhibited steadily high growth in the past 15 years, while the consumer price index (CPI) of water and sewage maintenance has outpaced the general CPI by an increasingly wide margin. This article employs a chained analysis method to examine water and wastewater rates for a group of utilities across US Census regions between 2000 and 2014. Results demonstrate that water and wastewater prices for this sample group have consistently increased and have surpassed CPI growth since 2006. Current and upcoming challenges facing water and wastewater utilities suggest that rate increases are likely to continue in the foreseeable future.